Japan : Report on Observance of Standards and Codes-Fiscal Transparency Module-Update. (IMF Staff Country Reports; Country Report ;, 2004)
This paper presents an update to Report on the Observance of Standards and Codes (ROSC)-Fiscal Transparency Module for Japan. Under the Fiscal Investment and Loan Program (FILP) reform initiated in 2001, the size of FILP has been significantly reduced. The government is moving toward privatizing four public highway corporations-recipients of large loans from the FILP-and the postal services. Efforts to minimize the use of supplementary budgets have been made. The economic and fiscal model underlying the medium-term macroeconomic and fiscal projections has been made available for open scrutiny.